VitalVizor A Visual Analytics System for Studying Urban Vitality - Zeng, Wei (IEEE computer graphics and applications, 2018)
Creating lively places with high urban vitality is an ultimate goal for urban planning and design. The VitalVizor visual analytics system employs well-established visualization and interaction techniques to facilitate user exploration of spatial physical entities and non-spatial urban design metrics when studying urban vitality